High-performance lead titanate piezoelectric ceramic and preparation method thereof
By incorporating specific ions and optimizing the preparation process, the phase structure and density of piezoelectric ceramics are improved, solving the problem of insufficient performance of existing piezoelectric ceramics and achieving higher electromechanical coupling coefficient and piezoelectric performance, making them suitable for ultrasonic testing.
Patent Information
- Application Number
- CN202411492009.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
AI Technical Summary
Existing piezoelectric ceramic materials and manufacturing processes limit their performance indicators, making it impossible to meet the requirements of high d33 and Kt being much higher than kp, and thus failing to meet the ultrasonic testing needs for high stability, detection rate, signal-to-noise ratio, and imaging quality.
Lattice distortion was adjusted by incorporating Ca2+, Ba2+, Sr2+, La3+, and Sm3+ ions, and the Ti4+ environment was altered by combining Co3+, Nb5+, W6+, and Mo6+. Magnesium oxide was used as a sintering aid and polyvinyl alcohol as a binder. The preparation process was optimized to improve the density and electromechanical coupling coefficient of piezoelectric ceramics.
The electromechanical coupling coefficient, d33, and g33 of the piezoelectric ceramic were improved, enhancing the piezoelectric performance and energy conversion efficiency, reducing dielectric loss, and achieving higher resolution and stronger energy conversion efficiency.
Smart Images

Figure BDA0005100326710000051 
Figure BDA0005100326710000061
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of piezoelectric ceramics, and in particular to a high-performance lead titanate piezoelectric ceramic and a preparation method thereof. Background Art
[0002] Ultrasonic testing is an important means of product quality inspection, control and improvement. With the emergence and development of various new materials, new structures and new processes, higher requirements are gradually put forward for ultrasonic testing methods. It is expected that ultrasonic testing will have higher stability, detection rate, signal-to-noise ratio, bandwidth and imaging quality to meet the detection and quantification of smaller defects, while also preventing the occurrence of missed detection, etc. As the core component of ultrasonic non-destructive testing transducers, the performance indicators of piezoelectric ceramics have a crucial impact on the sensitivity and resolution of the overall probe. The ideal situation is high Kt, low kp and high d33.
[0003] However, due to the limitations of current piezoelectric ceramic formula materials and preparation processes, the common lead titanate d33 on the market is only 75-80, and the kt is relatively small at only 0.52, and the kp is relatively large at 0.2, which cannot meet the indicators of high d33 and Kt far higher than kp. Summary of the invention
[0004] In order to improve the comprehensive piezoelectric performance of piezoelectric ceramics and increase parameters such as the electromechanical coupling coefficient of piezoelectric ceramics, the present application provides a high-performance lead titanate piezoelectric ceramic and a preparation method thereof.
[0005] In the first aspect, the present application provides a high-performance lead titanate piezoelectric ceramic, which adopts the following technical solution: A high-performance lead titanate piezoelectric ceramic with the molecular formula Pb 1-x A x Ti 1-y B y O3, wherein A is substituted Pb 2+ Ca 2+ , Ba 2+ , Sr 2+ ,La 3+ 、Sm 3+ At least one of the following, B is substituted for Ti 4+ Co 3+ , Nb 5+ , W 6+ 、Mo 6+ At least one of; wherein, 0.1<x≤0.3, 0<y≤0.08.
[0006] By adopting the above technical solution, Ca 2+ , Ba 2+ , Sr 2+ ,La 3+ 、Sm 3+With Pb 2+ The ionic radius of Co is different, and the appropriate amount of doping can cause lattice distortion, promote phase boundary movement, and then adjust the phase structure of piezoelectric ceramics, improve the dielectric and piezoelectric properties of piezoelectric ceramics, and increase the electromechanical coupling coefficient, d33, and g33. 3+ , Nb 5+ , W 6+ 、Mo 6+ The incorporation of Ti 4+ environment, increase the stability of the tetragonal phase, improve the dielectric, piezoelectric properties and stability of piezoelectric ceramics, and thus improve the resolution and piezoelectric properties of piezoelectric ceramics. By modifying lead titanate piezoelectric ceramics with elements such as niobium, calcium, cobalt, and tungsten, and adjusting the amount of each element added, the piezoelectric constant of piezoelectric ceramics can be improved, while increasing the density of piezoelectric ceramics, and improving the electromechanical coupling coefficient and energy conversion efficiency of piezoelectric ceramics.
[0007] Preferably, the lead titanate piezoelectric ceramic raw material includes Pb 1-x A x Ti 1-y B y O3, sintering aid and binder, wherein A is substituted for Pb 2+ Ca 2+ , Ba 2+ , Sr 2+ ,La 3+ 、Sm 3+ At least one of the following, B is substituted for Ti 4+ Co 3+ , Nb 5+ , W 6+ 、Mo 6+ At least one of; wherein, 0.1<x≤0.3, 0<y≤0.08.
[0008] By adopting the above technical solution, the sintering aid can reduce the sintering temperature, enhance the density of piezoelectric ceramics, reduce internal defects, increase the Curie temperature of the ceramic system, and improve the durability of piezoelectric ceramics. The binder can play the role of bonding powder in the piezoelectric ceramic process, promote ceramic molding, and enhance the density and piezoelectric properties of piezoelectric ceramics.
[0009] Preferably, the Pb 1-x A x Ti 1-y B y The mass ratio of O3, sintering aid and binder is 1:(0.01-0.03):(0.1-0.2).
[0010] Preferably, the sintering aid is magnesium oxide, and the binder is polyvinyl alcohol.
[0011] By adopting the above technical solution, magnesium oxide can form a liquid phase during the sintering process, reduce the sintering activation energy, reduce pores, enhance the density of ceramics, reduce internal defects, and improve the piezoelectric properties of ceramics. Polyvinyl alcohol enables the powder to maintain its shape during the pressing process, avoids deformation of the green body before sintering, promotes uniform particle distribution, and is beneficial to improving the density and piezoelectric properties of the sintered body.
[0012] In a second aspect, the present application provides a method for preparing high-performance lead titanate piezoelectric ceramics, using the following technical solution: A method for preparing high-performance lead titanate piezoelectric ceramics comprises the following specific steps: drying, ball milling, and crushing the raw materials at 0.3-1 t / cm 2 The ceramic blocks are pre-pressed and sintered to obtain ceramic blocks, which are then ground, centrifugally sprayed and granulated, and pressed into shape. The pressed ceramic blocks are subjected to binder removal, sintering and cooling, processing and forming, and electrode-coated to obtain electrode-coated ceramic sheets. The voltage is step-up to an electric field of 3-5 kv / mm in oil at 110-140°C, and the piezoelectric ceramics are polarized for 10-20 minutes.
[0013] By adopting the above technical solution, Pb 1-x A x Ti 1-y B y Drying, ball milling and crushing of O3 raw materials can refine raw material particles, improve the uniformity and activity of raw materials, enhance the specific surface area of raw materials, increase the density of piezoelectric ceramics, and thus improve the piezoelectric properties of piezoelectric ceramics. Debinding treatment can remove organic matter in green bodies, reduce the decomposition of organic matter during sintering to produce gas, lead to pores and defects, and thus reduce the generation of cracks in piezoelectric ceramics, and improve the density and piezoelectric properties of ceramics.
[0014] Preferably, the electrode comprises the following specific steps: cleaning the surface of the processed and shaped porcelain block, coating both sides with silver, and then calcining the silver at 760-840°C.
[0015] Preferably, the debinding temperature is 650-750°C.
[0016] Preferably, the ball milling medium in the ball milling process of the raw material is water, the particle size of the ball milling zirconium beads is 1-3 mm, and the ball milling particle size D50 in the ceramic block grinding process is 450-550 nm.
[0017] Preferably, the method comprises the following specific steps: 1-x A x Ti 1-y B y The O3 raw materials and sintering aids are dried, ball-milled, and crushed. After adding the binder, the mixture is heated to 0.3-1t / cm 2The ceramic blocks are pre-pressed and sintered to obtain ceramic blocks, which are then ground, centrifugally sprayed and granulated, and pressed into shape. The pressed ceramic blocks are subjected to binder removal, sintering and cooling, processing and forming, and electrode-coated to obtain electrode-coated ceramic sheets. The voltage is step-up to an electric field of 3-5 kv / mm in oil at 110-140°C, and the piezoelectric ceramics are polarized for 10-20 minutes.
[0018] In summary, this application has the following beneficial effects: 1. Since this application adopts Ca 2+ , Ba 2+ , Sr 2+ ,La 3+ 、Sm 3+ The addition of Co can adjust the phase structure of piezoelectric ceramics and improve the electromechanical coupling coefficient, d33 and g33 coefficients of piezoelectric ceramics. 3+ , Nb 5+ , W 6+ 、Mo 6+ The incorporation of Ti 4+ environment, which makes piezoelectric ceramics have higher energy conversion efficiency, higher resolution and enhanced piezoelectric properties of piezoelectric ceramics.
[0019] 2. In the present application, the raw materials are dried, ball-milled, crushed, pre-pressed and sintered to obtain ceramic blocks, and then the ceramic blocks are finely divided, centrifugal spray granulated, pressed into shape, debinding treated, sintered and cooled, processed into shape, electroded, and polarized to obtain piezoelectric ceramics. The preparation process is stable and easy to operate. Through the improvement of each process step, the piezoelectric ceramics can have a higher electromechanical coupling coefficient and piezoelectric constant and reduce dielectric loss. DETAILED DESCRIPTION
[0020] The present application is further described in detail below with reference to the embodiments.
[0021] All raw materials in the examples are commercially available. Example
[0022] Example 1 This embodiment provides a method for preparing a high-performance lead titanate piezoelectric ceramic, comprising the following specific steps: S1: Dry the raw materials at 120°C for 5 hours, weigh the raw materials Pb3O4, TiO2, CaCO3, CoCO3, and Nb2O5 according to the stoichiometric ratio to obtain the configured Pb 0.8 Ca 0.2 Ti 0.95 Co 0.05 Nb 0.02O3, the raw materials were ball-milled at a speed of 500 rpm for 2 hours, the ball-milling medium was water, the balls were zirconium balls, the ratio of zirconium balls was 3mm:2mm:1mm=2:3:5, and the ball-milling particle size D50 was controlled at 2μm. The mixed slurry was obtained, and then dried and crushed to obtain dry powder.
[0023] S2: Dry powder at 0.7t / cm 2 The ceramic block is then ground by a ball mill with a particle size D50 of 500 nm. The ball-milled slurry is subjected to centrifugal spray granulation to obtain granulated powder, which is then isostatically pressed at 200 MPa, debinded at 700 °C, sintered at 1200 °C for 1.5 h, and rapidly cooled at a rate of 200 °C / h to obtain a ceramic block.
[0024] S3: The ceramic block is processed by a cylindrical grinder and a double-sided grinder, and then ultrasonically cleaned. Double-sided silvering is performed by a screen printer, and then the silver is sintered at 800°C for 20 minutes. The obtained electrode ceramic piece is placed in oil at 120°C, step-by-step increased to 4kv / mm and polarized for 20 minutes to obtain a piezoelectric ceramic.
[0025] Example 2 The difference between Example 2 and Example 1 is that the high-performance lead titanate piezoelectric ceramic raw material is the configured Pb 0.8 Ba 0.2 Ti 0.9 Nb 0.08 O3.
[0026] Example 3 The difference between Example 3 and Example 1 is that the high-performance lead titanate piezoelectric ceramic raw material is the configured Pb 0.7 Sm 0.2 Ti 0.94 Co 0.05 Nb 0.02 O3.
[0027] Example 4 The difference between Example 4 and Example 1 is that the high-performance lead titanate piezoelectric ceramic raw material is the configured Pb 0.8 Ca 0.17 Ba 0.03 Ti 0.95 Nb 0.01 Co 0.03 W 0.015 O3.
[0028] Example 5 This embodiment provides a method for preparing a high-performance lead titanate piezoelectric ceramic, comprising the following specific steps: S1: Dry the raw materials at 120°C for 5h, weigh the raw materials Pb3O4, TiO2, CaCO3, CoCO3, Nb2O5, WO3, and BaCO3 according to the stoichiometric ratio to obtain the configured Pb 0.8 Ca 0.17 Ba 0.03 Ti 0.95 Nb 0.01 Co 0.03 W 0.015 O3, the raw material Pb 0.8 Ca 0.17 Ba 0.03 Ti 0.95 Nb 0.01 Co 0.03 W 0.015 O3 and sintering aids were ball milled at a speed of 500 rpm for 2 hours, the ball milling medium was water, the balls were zirconium balls, the ratio of zirconium balls was 3 mm: 2 mm: 1 mm = 2: 3: 5, and the ball milling particle size D50 was controlled at 2 μm. The mixed slurry was obtained, and then dried and crushed to obtain dry powder.
[0029] S2: Dry powder at 0.7t / cm 2 The ceramic block was pre-pressed under a pressure of 10000 ℃ and sintered at 850 ℃ for 2 hours to obtain a ceramic block. The ceramic block was then ground using a ball mill with a ball mill particle size D50 of 500 nm. The ball milled slurry was subjected to centrifugal spray granulation to obtain granulated powder. The granulated powder was mixed with a binder, and Pb 0.8 Ca 0.17 Ba 0.03 Ti 0.95 Nb 0.01 Co 0.03 W 0.015 The mass ratio of O3, sintering aid and binder is 1:0.01:0.15, wherein the sintering aid is magnesium oxide and the binder is polyvinyl alcohol. Then, isostatic pressing is performed at 200MPa, followed by binder removal at 700℃, sintering at 1200℃ for 1.5h, and rapid cooling at a rate of 200℃ / h to obtain a ceramic block.
[0030] S3: The ceramic block is processed by a cylindrical grinder and a double-sided grinder, and then ultrasonically cleaned. Double-sided silvering is performed by a screen printer, and then the silver is sintered at 800°C for 20 minutes. The obtained electrode ceramic piece is placed in oil at 120°C, step-by-step increased to 4kv / mm and polarized for 20 minutes to obtain a piezoelectric ceramic.
[0031] Example 6 The difference between Example 6 and Example 5 is that in the preparation method of high-performance lead titanate piezoelectric ceramics, Pb 0.8 Ca 0.17 Ba 0.03 Ti0.95 Nb 0.01 Co 0.03 W 0.015 The mass ratio of O3, sintering aid and binder is 1:0.01:0.1.
[0032] Example 7 The difference between Example 7 and Example 5 is that in the preparation method of high-performance lead titanate piezoelectric ceramics, Pb 0.8 Ca 0.17 Ba 0.03 Ti 0.95 Nb 0.01 Co 0.03 W 0.015 The mass ratio of O3, sintering aid and binder is 1:0.02:0.2.
[0033] Example 8 The difference between Example 8 and Example 7 is that in the preparation method of high-performance lead titanate piezoelectric ceramics, Pb 0.8 Ca 0.17 Ba 0.03 Ti 0.95 Nb 0.01 Co 0.03 W 0.015 The mass ratio of O3, sintering aid and binder is 1:0.03:0.1.
[0034] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the raw material of the high-performance lead titanate piezoelectric ceramic is Pb 0.91 La 0.03 Ti 0.9 Mn 0.1 O3.
[0035] The preparation method of high-performance lead titanate piezoelectric ceramics comprises the following specific steps: S1: Dry all raw materials at 120°C for 5h, weigh Pb3O4, TiO2, MnO2, and La2O3 in the chemical formula molar mass ratio, and mix the raw materials by ball milling at a speed of 500rpm for 2h. The ball milling medium is water, the balls are zirconium balls, the zirconium ball ratio is 3mm:2mm:1mm=2:3:5, and the ball milling particle size D50 is controlled at 2μm. The mixed slurry is obtained, and then dried and crushed to obtain dry powder.
[0036] S2: Dry powder at 0.7t / cm 2The ceramic block is then ground by a ball mill with a particle size D50 of 500 nm. The ball-milled slurry is subjected to centrifugal spray granulation to obtain granulated powder, which is then isostatically pressed at 200 MPa, debinded at 700 °C, sintered at 1200 °C for 1.5 h, and rapidly cooled at a rate of 200 °C / h to obtain a ceramic block.
[0037] S3: The ceramic block is processed by a cylindrical grinder and a double-sided grinder, and then ultrasonically cleaned. Double-sided silvering is performed by a screen printer, and then the silver is sintered at 800°C for 20 minutes. The obtained electrode ceramic piece is placed in oil at 120°C, step-by-step increased to 4kv / mm and polarized for 20 minutes to obtain a piezoelectric ceramic.
[0038] Performance testing The following performance tests were conducted on the high-performance lead titanate piezoelectric ceramics provided in Examples 1-8 of the present application and Comparative Example 1. The specific test results are shown in Table 1.
[0039] Detection Methods The piezoelectric ceramic sheet prepared in this application was left to stand at room temperature for 24 hours before the piezoelectric performance was tested. The radial resonance frequency f of the Φ20 mm×1 mm piezoelectric ceramic element was measured using an impedance analyzer TH2839. a , anti-resonance frequency f r , dielectric loss tanδ, calculate the thickness direction, radial electromechanical coupling coefficient, and dielectric constant ε 33 The piezoelectric constant d33 of Φ20mm×1mm piezoelectric ceramic elements was tested using a ZJ-6 quasi-static d33 measuring instrument.
[0040] Table 1: Performance test results data table From the performance test results, it can be seen that the present application uses niobium, calcium, cobalt, tungsten and other elements to modify the lead titanate piezoelectric ceramics, and adjusts the doping amount of each element at the same time. The obtained piezoelectric ceramics have good piezoelectric properties, higher electromechanical coupling coefficient, higher d33 and resolution, stronger energy conversion efficiency, and can be better applied in ultrasonic non-destructive testing of tiny defects. By comparing the comparative example with Example 1, it can be seen that the piezoelectric performance of the piezoelectric ceramics prepared by lead titanate in Comparative Example 1, the performance indicators cannot meet the requirements of high resolution, and cannot effectively identify tiny defects.
[0041] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-performance lead titanate piezoelectric ceramic, characterized in that: The molecular formula is Pb 1-x A x Ti 1-y B y O3, wherein A is substituted Pb 2+ Ca 2+ , Ba 2+ , Sr 2+ ,La 3+ 、Sm 3+ At least one of the following, B is substituted for Ti 4+ Co 3+ , Nb 5+ , W 6+ 、Mo 6+ At least one of; wherein, 0.1<x≤0.3, 0<y≤0.
08.
2. The high performance lead titanate piezoelectric ceramic according to claim 1, characterized in that: The lead titanate piezoelectric ceramic raw material includes Pb 1-x A x Ti 1-y B y O3, sintering aid and binder, wherein A is substituted for Pb 2+ Ca 2+ , Ba 2+ , Sr 2+ ,La 3+ 、Sm 3+ At least one of the following, B is substituted for Ti 4+ Co 3+ , Nb 5+ , W 6+ 、Mo 6+ At least one of; wherein, 0.1<x≤0.3, 0<y≤0.
08.
3. The high performance lead titanate piezoelectric ceramic according to claim 2, characterized in that: The Pb 1-x A x Ti 1-y B y The mass ratio of O3, sintering aid and binder is 1: (0.01-0.03): (0.1-0.2).
4. The high performance lead titanate piezoelectric ceramic according to claim 2, characterized in that: The sintering aid is magnesium oxide, and the binder is polyvinyl alcohol.
5. A method for preparing a high-performance lead titanate piezoelectric ceramic according to any one of claims 1 to 4, characterized in that: The specific steps include: drying, ball milling and crushing the raw materials at 0.3-1t / cm 2 The ceramic blocks are pre-pressed and sintered to obtain ceramic blocks, which are then ground, centrifugally sprayed and granulated, and pressed into shape. The pressed ceramic blocks are subjected to binder removal, sintering and cooling, processing and forming, and electrode-coated to obtain electrode-coated ceramic sheets. The voltage is step-up to an electric field of 3-5 kv / mm in oil at 110-140°C, and the piezoelectric ceramics are polarized for 10-20 minutes.
6. The method for preparing high-performance lead titanate piezoelectric ceramics according to claim 5, characterized in that: The electrode method comprises the following specific steps: ultrasonically cleaning the surface of the processed ceramic block, coating both sides with silver, and then calcining the silver at 760-840°C.
7. The method for preparing high-performance lead titanate piezoelectric ceramics according to claim 5, characterized in that: The debinding temperature is 650-750°C.
8. The method for preparing high-performance lead titanate piezoelectric ceramics according to claim 5, characterized in that: The ball milling medium in the raw material ball milling process is water, the particle size of the ball milling zirconium beads is 1-3 mm, and the ball milling particle size D50 in the ceramic block fine grinding process is 450-550 nm.
9. The method for preparing high-performance lead titanate piezoelectric ceramics according to claim 5, characterized in that: The specific steps include: 1-x A x Ti 1-y B y The O3 raw materials and sintering aids are dried, ball-milled, and crushed. After adding the binder, the mixture is heated to 0.3-1t / cm 2 The ceramic blocks are pre-pressed and sintered to obtain ceramic blocks, which are then ground, centrifugally sprayed and granulated, and pressed into shape. The pressed ceramic blocks are subjected to binder removal, sintering and cooling, processing and forming, and electrode-coated to obtain electrode-coated ceramic sheets. The voltage is step-up to an electric field of 3-5 kv / mm in oil at 110-140°C, and the piezoelectric ceramics are polarized for 10-20 minutes.
Citation Information
Patent Citations
Strontium and barium doping lead niobium-stibium zirconate-titanate series piezoelectric ceramic and preparation method thereof
CN101265090A
Piezoelectric ceramic applied to electronic betel nuts, and manufacturing method thereof
CN110668815A
Lanthanum lead zirconate titanate-based piezoelectric ceramic as well as preparation method and application thereof
CN111908915A